Ответы и объяснения

2014-02-21T15:36:26+00:00
1)(x+3+ (9/(x-3))* (5x-15)/x^2=(((x+3)(x-3)+9)/(x-3))*(5x-15)/x^2=(x^2/(x-3))*(5x-15)/x^2=(5x-15)/(x-3)=5(x-3)/(x-3)=5
2)(x^2-4)*( (3x+1)/(x^2-4)= ((x^2-4)/1)*( 3x+1)/(x^2-4)=3x+1
3)( (2x-y)/(2x+y)-(2x+y)/(2x-y))*( (6x+12)/x^2)=( (4x^2-2xy-2xy+y^2-4x^2-2xy-2xy-y^2)*(6x+12))/(4x^2-y^2)*x=(- 48xy-96)/((4x^2-y^2)*(x))
 с-15
(4x+2)/(2x-3)+(x-17)/(3-2x)=(4x+2-x+17)/(2x-3)=(3x-19)/(2x-3)
(1-2x)/(4x-3)-(3+x)/(3-4x)=(1-2x+3+x)/(4x-3)=(-x+4)/(4x-3)
(2x+13)/(x+5)+(2+x)/(x+5)= (2x+13+2+x)/(x+5)=(3x+15)/(x+5)
(4x-1)/(3x-7)+(13-2x)/(7-3x)=(4x-1-13+2x)/(3x-7)=(6x-14)/(3x-7)
 (7x-11)/(x-4)-(13+x)/(x-4)=(7x-11-13-x)/(x-4)=(6x-24)/(x-4)=6(x-4)/(x-4)=6
(5x-6)/(x^2-3xy)-(5y-2)/(xy-3y^2)=(5xy-6y-5xy+2x)/(xy(x-3y))=(-6y+2x)/(xy(x-3))



Комментарий удален
могу
Комментарий удален